(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The landscape of work is undergoing a transformative shift with the growing prevalence of far flung work. This review paper explores the drivers at the back of the adoption of far off paintings, analyzes its blessings and demanding situations, and examines its profound implications on organizational systems